Ai Superpowers : China, Silicon Valley, and the New World Order. - Lee, Kai-Fu. (HarperCollins Publishers, 2018)
A New York Times Bestseller One of the world's most respected experts on AI and China reveals that China has suddenly caught up to the United States at an astonishingly rapid and unexpected pace.